Hypermethylation and loss of retinoic acid receptor responder 1 expression in human choriocarcinoma - Hübner, Hanna; Strick, Reiner; Wachter, David Lukas; Kehl, Sven; Strissel, Pamela; Schneider-Stock, Regine; Rascher, Wolfgang; Horn, L. C.; Beckmann, Matthias; Rübner, Matthias; Fahlbusch, F. B.; Hartner, Andrea (Journal of Experimental & Clinical Cancer Research, 2017)
BACKGROUND: Human placental development resembles tumorigenesis, due to the invasive and fusogenic potential of trophoblasts. However, these features are tightly controlled in trophoblasts. Disturbance of this spatial and temporal regulation is thought to contribute to the rare formation of choriocarcinomas. Promoter hypermethylation and loss of the tumor suppressor Retinoic acid receptor responder 1 (RARRES1) were shown to contribute to cancer progression. Our study investigated the epigenetic and transcriptional regulation of RARRES1 in healthy human placenta in comparison to choriocarcinoma cell lines and cases. METHODS: Three choriocarcinoma cell lines (Jeg-3, JAR and BeWo) were treated with three different retinoic acid derivates (Am580, Tazarotene and all-trans retinoic acid) and 5-aza-2'-deoxycytidine. We analyzed RARRES1 promoter methylation by pyrosequencing and performed realtime-PCR quantification to determine RARRES1 expression in placental tissue and trophoblastic cell lines. Additionally, RARRES1 was stained in healthy placentas and in biopsies of choriocarcinoma cases (n = 10) as well as the first trimester trophoblast cell line Swan71 by immunofluorescence and immunohistochemistry. RESULTS: In the choriocarcinoma cell lines, RARRES1 expression could not be induced by sole retinoic acid treatment. Stimulation with 5-aza-2'-deoxycytidine significantly induced RARRES1 expression, which then could be further increased with Am580, Tazarotene and all-trans retinoic acid. In comparison to healthy placenta, choriocarcinoma cell lines showed a hypermethylation of the RARRES1 promoter, which correlated with a reduced RARRES1 expression. In concordance, RARRES1 protein expression was lost in choriocarcinoma tissue. Additionally, in the trophoblastic cell line Swan71, we found a significant induction of RARRES1 expression with increased cell density, during mitosis and in syncytial knots. CONCLUSIONS: Our findings showed that RARRES1 expression is absent in choriocarcinoma due to promoter methylation. Based on our analysis, we hypothesize that RARRES1 might exert tumor suppressive functions in multiple cellular processes (e.g. cell cycle regulation, adhesion, invasion and apoptosis).
EVALuna2:33950